2015
DOI: 10.3233/bmr-140555
|View full text |Cite
|
Sign up to set email alerts
|

Age-related progressive increase of lower back pain among male dance sport competitors

Abstract: Lower back pain is propounding health problem in male dancers and increases with age that cannot be resolved by decreasing training intensity. This research reveals that only 28% of male dancers will seek medical help because of occurrence of musculoskeletal pain. Multidisciplinary approach with the aim of long-term health protection and prolongation of dancing careers is required in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
3
1
1
Order By: Relevance
“…Studies evaluating aerobic, 26 ballroom, 25 and Zumba ®15,27 dance indicate that age does not predict dance-related injury. Despite these, and our own, findings, Miletic et al 28 demonstrated a moderate relationship between increasing age and lower back pain prevalence in ballroom dance. In the current sample of salsa dancers, injury risk increased with increasing BMI.…”
Section: Discussioncontrasting
confidence: 93%
“…Studies evaluating aerobic, 26 ballroom, 25 and Zumba ®15,27 dance indicate that age does not predict dance-related injury. Despite these, and our own, findings, Miletic et al 28 demonstrated a moderate relationship between increasing age and lower back pain prevalence in ballroom dance. In the current sample of salsa dancers, injury risk increased with increasing BMI.…”
Section: Discussioncontrasting
confidence: 93%
“…6,7,28 In one study, the knee of competitive male dancers aged from 15 to 17 years was the most frequent pain region with 44.7% of the total, and the second most frequent pain region with 49.3% in the age group above 25 years. 11 Even in male ballet dancers, the knee has been found to be more frequently affected than in females (female: 11.5%; male: 15.2%). 29 Miletic et al 6 cited the turnout performed in rapid rhythms by standard and Latin male dancers as a cause of hip problems.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 Two studies in dancesport used the Self-Estimated Functional Inability Because of Pain (SEFIP) test to measure pain intensity in different body regions in relation to performance capability. 6,11 Dancelimiting pain (levels 3 and 4) was rare 6,11 ; thus, only 3 out of 86 standard and Latin dancers had to avoid certain movements due to pain. 6 Continuing to dance despite being in pain is a frequently practiced behavior in dance.…”
mentioning
confidence: 99%
“…68 This contrasts results in gendered sports like rhythmic gymnasts, Dance Sport, and similar disciplines where there is an increased their risk of LBP with age. [69][70][71][72] We were unable to determine a conclusive link between certain ages and risks for LBP/LBI from the results of this study. Studies did not specify the age range of those dancers who either became injured or had endured/still endure back pain; demographics for the general population were provided, but none for those dancers that actually endured LBP or LBI.…”
Section: Agementioning
confidence: 92%